Arbitražna klavzula v ustanovitvenih aktih gospodarskih družb - Podgorelec, Peter (Podjetje in delo, 2013)
Due certain advantages (discretion, speed, professionalism etc.) the arbitration procedure is recommended also for the settlement of corporate disputes. In general, Slovenian legislation provides for an adequate current regulatory framework, taking into account, of course, the classic rules of thearbitration law, in particular the assumptions for the arbitral tribunal toaccept jurisdiction (the existence of the arbitration agreement and the dispute arbitrability) as well as legal nature of an arbitration clause.
Keywords: arbitraža; arbitražni postopki; gospodarske družbe; reševanje; spori